1961
DOI: 10.2307/3895072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Supplemental Run-Off Water and Fertilizer on Production and Chemical Composition of Native Forage

Abstract: Utilization of runoff water to produce additional forage is essential in a balanced range management program. This. is especially true in the northern Great Plains where limited and erratic precipitation results in frequent drought periods. The use of water spreading systems to collect and distribute runoff water over "run-in" range sites has generally resulted in greater forage production (Mooney and Martin, 1956). However, the extra moisture received on several "run-in" range sites on the heavy clay soils of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…& J.G.Smith) Gould] wheatgrasses increased, and weeds often invaded. Cosper and Thomas (1961). Hyder and Bement (1964) and Patterson and Youngman (1960) found that weeds often increased in response to N to the extent that desirable species could not compete.…”
mentioning
confidence: 99%
“…& J.G.Smith) Gould] wheatgrasses increased, and weeds often invaded. Cosper and Thomas (1961). Hyder and Bement (1964) and Patterson and Youngman (1960) found that weeds often increased in response to N to the extent that desirable species could not compete.…”
mentioning
confidence: 99%
“…Similarly, results from a 6-year study in North Dakota showed that 2 years of fertilization, with 90 lb of nitrogen on a heavily grazed pasture, did more to improve range condition and production than did 6 years without grazing (Rogler and Lorenz, 1957). Studies in western South Dakota indicated that maximum forage production from utilizing runoff water could not be obtained without fertilization (Cosper and Thomas, 1961).…”
mentioning
confidence: 99%
“…Other investigators have shown that the results of fertilizer application depend on the moisture supply and the species present. Cosper and Thomas ( 1) found that supplemental moisture increased the efficiency of nitrogen fertilizer but decreased the effectiveness of phosphate on western South Dakota range. They found that annual forbs responded to nitrogen better than to phosphate whereas 79 Willhite et al ( 6) had reported that forbs responded to phosphate more than to nitrogen in irrigated mountain meadows.…”
mentioning
confidence: 99%